2019
DOI: 10.1111/joor.12916
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lip motion detected with a compact 3D camera and swallowing dynamics during bolus flow swallowing in Japanese elderly men

Abstract: Clinical application of a swallowing function evaluation system that is minimally invasive and enables an objective evaluation is necessary. We constructed a system that can synchronise and analyse lip motion with a three‐dimensional (3D) camera and swallowing dynamics with videofluoroscopy (VF) and clarified the relationship between lip movement and swallowing dynamics. A compact 3D camera was adapted to Microsoft XBox One Kinect Sensor®. We examined Kinect's accuracy and repeatability and analysed the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It is important to point out the limitations of this study. Even though similar sample sizes have been reported in other studies, 1,16 it may be necessary to recruit and investigate more patients using the protocol of the present study. This may provide a better understanding of the relationship between clinical findings and motion.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…It is important to point out the limitations of this study. Even though similar sample sizes have been reported in other studies, 1,16 it may be necessary to recruit and investigate more patients using the protocol of the present study. This may provide a better understanding of the relationship between clinical findings and motion.…”
Section: Discussionmentioning
confidence: 76%
“…12 As for the reproducibility of the measurement device used in this study, several papers have been reported so far. 10,13,14,16 In the study of 3D measurement, the reproducibility of measurement points has always been a subject of debate. However, the majority of the reports on the system and reproducibility in 3D measurement research are based on the measurement accuracy of the measuring instruments, and the measurement error is said to be within 0.3 mm due to the progress in the development of the measuring instruments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, the soft tissue information on the fluoroscopic image is extremely unclear. Moreover, the movement of the facial surface, including the lips, affects the swallowing movement of the oral cavity and pharynx 8,9 . The VFSS is performed using an X-ray fluoroscopic unit that depicts bone and unclear soft tissue.…”
Section: Discussionmentioning
confidence: 99%